African Development Bank group policy on good governance - African development bank; African Development Bank.; African Development Fund. (Abidjan : African Development Bank, African Development Fund, 1965)
This book provides insight into the origin, the background, the composition, the policies and general administrative principles of the African development bank.
Cover title.
asm; 05/03/19
Loans
Keywords: Economic development projects; Africa